Reply to the 'Comment on "A universal approach for calculating the Judd–Ofelt parameters of RE3+ in powdered phosphors and its application for the β-NaYF4:Er3+/Yb3+ phosphor derived from auto-combustion-assisted fluoridation"' by D. Zhang, Q. Xu and Y. Zhang, Phys. Chem. Chem. Phys., 2019, 21, DOI: 10.1039/C8CP07577H. Issue 20 (15th May 2019) - Zhang, Yanqiu; Chen, Baojiu; Xu, Sai; Li, Xiangping; Zhang, Jinsu; Sun, Jiashi; Zhang, Xiangqing; Xia, Haiping; Hua, Ruinian
Abstract : This is a Reply to the corresponding Comment and the strategy for the application of Judd–Ofelt theory was discussed. Abstract : In this Reply, we truthfully respond to the comments on our recent paper entitled "A universal approach for calculating the Judd–Ofelt parameters of RE 3+ in powdered phosphors and its application for the β-NaYF4 :Er 3+ /Yb 3+ phosphor derived from auto-combustion-assisted fluoridation" published in Phys. Chem. Chem. Phys. [Y. Zhang, B. Chen, S. Xu, X. Li, J. Zhang, J. Sun, X. Zhang, H. Xia, R. Hua, A universal approach for calculating the Judd–Ofelt parameters of RE3+ in powdered phosphors and its application for the beta-NaYF4:Er3+/Yb3+ phosphor derived from auto-combustion-assisted fluoridation, Phys. Chem. Chem. Phys., 20, 2018, 15876–15883]. In the Comment, the authors oppugned partial calculation results we reported in our original paper, thus we redid the calculations and compared the presently obtained results with the original ones and the author provided ones. The recalculations and comparisons confirmed that our calculations are reproducible and the results are correct. In the Comment, the authors also made some comments on the Judd–Ofelt calculation approaches for powdered samples reported by other researchers. Following the authors' train of thought we added some supplements to the comments to understand the application strategy of Judd–Ofelt theory. Furthermore, we extended some points of view regarding the fluorescence lifetime measurements the authors presented in the Comment.